Review of Audiovestibular Symptoms Following Exposure to Acoustic and Electromagnetic Energy Outside Conventional Human Hearing - Lubner, Rory J.; Kondamuri, Neil S.; Knoll, Renata M.; Ward, Bryan K.; Littlefield, Philip D.; Rodgers, Derek; Abdullah, Kalil G.; Remenschneider, Aaron K.; Kozin, Elliott D. (Frontiers in Neurology, 2020)
Objective: We aim to examine the existing literature on, and identify knowledge gaps in, the study of adverse animal and human audiovestibular effects from exposure to acoustic or electromagnetic waves that are outside of conventional human hearing. Design/Setting/Participants: A review was performed, which included searches of relevant MeSH terms using PubMed, and Embase Scopus. Primary outcomes included documented auditory and/or vestibular signs or symptoms in animals or humans exposed to infrasound, ultrasound, radiofrequency, and magnetic resonance imaging. The references of these articles were then reviewed in order to identify primary sources and literature not captured by electronic search databases. Results: Infrasound and ultrasound acoustic waves have been described in the literature to result in audiovestibular symptomology following exposure. Technology emitting infrasound such as wind turbines and rocket engines have produced isolated reports of vestibular symptoms, including dizziness and nausea and auditory complaints, such as tinnitus following exposure. Occupational exposure to both low frequency and high frequency ultrasound has resulted in reports of wide-ranging audiovestibular symptoms, with less robust evidence of symptomology following modern-day exposure via new technology such as remote controls, automated door openers, and wireless phone chargers. Radiofrequency exposure has been linked to both auditory and vestibular dysfunction in animal models, with additional historical evidence of human audiovestibular disturbance following unquantifiable exposure. While several theories, such as the cavitation theory, have been postulated as a cause for symptomology, there is extremely limited knowledge of the pathophysiology behind the adverse effects that particular exposure frequencies, intensities and durations have on animals and humans. This has created a knowledge gap in which much of our understanding is derived from retrospective examination of patients who develop symptoms after postulated exposures. Conclusion and Relevance: Evidence for adverse human audiovestibular symptomatology following exposure to acoustic waves and electromagnetic energy outside the spectrum outside the spectrum of human hearing is largely rooted in case series or small cohort studies. Further research on the pathogenesis of audiovestibular dysfunction following acoustic exposure to these frequencies is critical to understand reported symptoms.